The serpent's secret - DasGupta, Sayantani (DasGupta, Sayantani. Kiranmala and the kingdom beyond, 2019)
Up until her twelfth birthday, Kiranmala considered herself an ordinary sixth-grader in Parsippany, New Jersey, but then her parents disappear and a drooling rakkhosh demon shows up in her kitchen, and soon she is swept into another dimension, full of magic, winged horses, talking birds (very annoying), and cute princes--and somehow Kiranmala needs to sort it all out, find her parents, and basically save the world.